A Chiral Molecular Cage Comprising Diethynylallenes and N-Heterotriangulenes for Enantioselective Recognition - Miguez-Lago, Sandra; Gliemann, Bettina; Kivala, Milan; Cid, Maria Magdalena (Chemistry - A European Journal, 2021)
Chirality, a characteristic tool of molecular recognition in nature, is often a complement of redox active systems. Scientists, in their eagerness to mimic such sophistication, have designed numerous chiral systems based on molecular entities with cavities, such as macrocycles and cages. In an attempt to combine chirality and redox-active species, in this contribution we report the synthesis and detailed characterization of a chiral shape-persistent molecular cage based on the combination of enantiopure diethynylallenes and electron-rich bridged triarylamines, also known as N-heterotriangulenes. Its ability for chiral recognition in solution was revealed through UV/vis titrations with enantiopure helicenes.
CRIS-Team Scopus Importer:2021-08-20
Keywords: allenes; bridged triarylamines; chirality; molecular cages; molecular recognition

Binary supramolecular networks of bridged triphenylamines with different substituents and identical scaffolds - Steiner, Christian; Yang, Zechao; Gliemann, Bettina; Meinhardt, Ute; Gurrath, Martin; Ammon, Maximilian Michael; Meyer, Bernd; Kivala, Milan; Maier, Sabine (Chemical Communications, 2018)
Based on scanning tunneling microscopy experiments combined with density functional theory, we report the formation and the electronic structure of porous binary supramolecular networks on Au(111). The two triphenylamine derivatives with identical scaffolds intermix due to a maximization of the overall number of H-bonds instead of an optimization of the H-bond strength in the bonding motif. The HOMO-LUMO gap is defined by both molecules, which is typical for electron donor-acceptor networks.

Configurationally Stable Chiral Dithia-Bridged Hetero[4]helicene Radical Cation: Electronic Structure and Absolute Configuration - Gliemann, Bettina; Petrovic, Ana G.; Zolnhofer, Eva; Dral, Pavlo O.; Hampel, Frank; Breitenbruch, Georg; Schulze, Philipp; Raghavan, Vijay; Meyer, Karsten; Polavarapu, Prasad L.; Berova, Nina; Kivala, Milan (Chemistry - An Asian Journal, 2017)
A stable chiral hetero[4]helicene radical cation was synthesized and characterized by UV/Vis absorption and EPR spectroscopy, as well as X-ray crystallography. For the first time, a combination of chiroptical methods involving ECD, ORD, and VCD, supported by quantum mechanical predictions, enabled the elucidation of the absolute configuration of such open-shell helical species.
EAM Import::2019-03-13

Dithiafulvenyl-Extended N-Heterotriangulenes and Their Interaction with C60: Cooperative Fluorescence - Gliemann, Bettina; Strauß, Volker; Hitzenberger, Jakob; Dral, Pavlo O.; Hampel, Frank; Gisselbrecht, Jean-Paul; Drewello, Thomas; Thiel, Walter; Guldi, Dirk Michael; Kivala, Milan (Chemistry - A European Journal, 2017)
We describe the synthesis as well as the electronic and photophysical characterization of novel N-heterotriangulene derivatives decorated with methoxycarbonyl- and methyl-sulfanyl-substituted dithiafulvenyl moieties. The association of these electron-rich compounds with fullerene C60 as electron acceptor was investigated by means of photophysical, voltammetric, and mass spectrometric methods and rationalized by DFT calculations. Importantly, light-induced interactions between the dithiafulvene-substituted N-heterotriangulene bearing methoxycarbonyl substituents with C60 leads to cooperative fluorescence. Quantitative Job plot analyses by means of fluorescence spectroscopy and voltammetry confirm a 1:1 association with binding constants in the order of 104 m-1. Supportive results for the supramolecular assembly of both N-heterotriangulenes with C60 were obtained by ESI mass spectrometric investigations in the gas phase.
EAM Import::2019-03-13

Self-Assembly and Stability of Hydrogen-Bonded Networks of Bridged Triphenylamines on Au(111) and Cu(111) - Steiner, Christian; Gliemann, Bettina; Meinhardt, Ute; Gurrath, Martin; Meyer, Bernd; Kivala, Milan; Maier, Sabine (Journal of Physical Chemistry C, 2015)
The adsorption, chemical nature, and self-assembly of diaminotriazinyl- and carboxyl-substituted triphenylamines with dimethylmethylene bridges were studied on Au(111) and Cu(111) at submonolayer coverage by low-temperature scanning tunneling microscopy and density functional theory. On Au(111), both molecules form extended porous honeycomb networks. The geometry of the networks agrees well with density functional theory optimized hydrogen-bonded gas phase structures. Therefore, the self-assemblies on Au(111) are strongly directed by intermolecular hydrogen bond interactions. In contrast, on Cu(111) both molecules aggregate in dense islands owing to the stronger moleculesurface interaction. While the carboxyl substituents partially deprotonate at room temperature on Cu(111), the diaminotriazinyl-substituted triphenylamines adsorb mainly intact. The diaminotriazinyl groups deprotonate gradually at increased adsorption temperatures.